Former Yugoslav Republic of Macedonia : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the former Yugoslav Republic of Macedonia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The staff report for the 2008 Article IV Consultation of the Former Yugoslav Republic of Macedonia discusses economic developments and policies. The new government's economic program aims to raise growth further, but does not address these vulnerabilities. Plans to increase the central government deficit permanently to about 2 percent of GDP or perhaps even higher risk worsening external vulnerabilities. The main risk to growth and macroeconomic stability is the widening current account deficit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet